Предмет:
Другие предметыАвтор:
анонимЕK = (m * V2)/2 (кинетическая энергия);
V= √((2 * Eк)/m);(m * V2)/R = e * B * V (1 случай); m * V = e * B * R (2 случай);
m * √((2*Ек1 )/m) = e * B * R1 (1 случай);m * √((2*Eк2)/m) = e * B * R2 (2 случай);Найдем соотношение первого и второго случая: R1/R2 = √(Ек1 / Ек2), потому что V = (2 * pi * R)/T, то:T1/T2 = ((2 * pi * R1)/V1) / ((2 * pi * R2)/V2) = (R1 * V2)/(R2 * V1) = Eк1/Ек2.
Автор:
winston35Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть